SISTEM INFORMASI GEOGRAFIS REKOMENDASI SERVIS KOMPUTER BERBASIS ANDROID: METODE MULTI ATTRIBUTE UTILITY THEORY DAN ALGORITMA A-STAR: GEOGRAPHIC INFORMATION SYSTEM FOR COMPUTER SERVICE RECOMMENDATION BASED ON ANDROID: MULTI ATTRIBUTE UTILITY THEORY METHOD AND A-STAR ALGORITHM - Walad Hidayat; Zara Yunizar; Nunsina (LPPM Universitas Abdurrab, 2025)
This study developed an Android-based Geographic Information System to recommend computer repair service shops in Lhokseumawe City, addressing the gap in previous studies that have not integrated recommendation and route-finding systems into a single mobile application. Data were collected through surveys of 17 active shops using weighted questionnaires and interviews. The Multi Attribute Utility Theory (MAUT) method is used to evaluate seven criteria, such as years of operation, repair coverage, spare part availability, service cost, warranty, number of technicians, and rating. The A-Star algorithm was applied to calculate the shortest route based on GPS coordinates. Results showed that “JCom” achieved the highest recommendation score (0.810), and the optimal route from the starting point (Informatics Engineering Building, Unimal) to the selected shop was 11,793.74 meters, based on node accumulation. The system proved effective in providing accurate recommendations and efficient navigation, assisting users in choosing the best service shop through a single Android application.